Pengetahuan Tentang Gangguan Jiwa Berhubungan Dengan Sikap Masyarakat Pada Penderita Gangguan Jiwa - Nuria Muliani; Tri Rahma Yanti (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: to identify  Relationships Of Knowledge About Mental Disorders with Community Attitudes To Students Disorders In Work Areas Batanghari Health CenterMethods: This article subject of this study was the community in the work area of the Batnghari Community Health Center by sampling using the Accidental Sampling technique. This research uses cross sectional method which is done by survey technique using chi square analysis. The tool used in data collection is a questionnaire with a sample size of 90 respondents. The purpose of this study was to determine whether there is a relationship between knowledge about mental disorders and social attitudes of people with mental disorders in the work area of Batanghari Public Health Center.Results:  Based on the Chi-Square test, it was found that there was a significant relationship between the relationship of knowledge about mental disorders to community attitudes towards mental disorders in the Batanghari Community Health Center in 2020 with a p-value (0,000), which means <5% (0.005) this study shows that Ho was successfully rejected.